Simultaneous Improvement in Efficiency and Stability of Low‐Temperature‐Processed Perovskite Solar Cells by Interfacial Control. Issue 14 (24th January 2018) - Azmi, Randi; Lee, Chang‐Lyoul; Jung, In Hwan; Jang, Sung‐Yeon
Abstract: In most current state‐of‐the‐art perovskite solar cells (PSCs), high‐temperature (≈500 °C)‐sintered metal oxides are employed as electron‐transporting layers (ETLs). To lower the device processing temperature, the development of low‐temperature‐processable ETL materials (such as solution‐processed ZnO) has received growing attention. However, thus far, the use of solution‐processed ZnO is limited because the reverse decomposition reaction that occurs at ZnO/perovskite interfaces significantly degrades the charge collection and stability of PSCs. In this work, the reverse decomposition reaction is successfully retarded by sulfur passivation of solution‐processed ZnO. The sulfur passivation of ZnO by a simple chemical means, efficiently reduces the oxygen‐deficient defects and surface oxygen‐containing groups, thus effectively preventing reverse decomposition reactions during and after formation of the perovskite active layers. Using the low‐temperature‐processed sulfur‐passivated ZnO (ZnO–S), perovskite layers with higher crystallinity and larger grain size are obtained, while the charge extraction at the ZnO/perovskite interface is significantly improved. As a result, the ZnO–S‐based PSCs achieve substantially improved power‐conversion‐efficiency (PCE) (19.65%) and long‐term air‐storage stability (90% retention after 40 d) compared with pristine ZnO‐based PSCs (16.51% and 1% retention after 40 d). Notably, the PCE achieved is the highest recorded (19.65%) for low‐temperature ZnO‐based PSCs. Abstract : Air‐stable high efficiency perovskite solar cells are developed using sulfur‐passivated ZnO electron transport layers. Sulfur passivation of ZnO effectively prevents the interfacial reverse reaction from perovskite to PbI2, while the surface hydrophobicity of ZnO is increased. The results show that the quality of perovskite layers is improved and the interfacial charge recombination is reduced.